The mechanism of practicing Tai Chi to prevent falls in the elderly - Dong, Kun; Wang, Lin (The Journal of the International Society of Chinese Health Practices, 2021)
Objective: At present, the fall of the elderly has become a serious public health problem; and, with the acceleration of aging, the incidence of falls of the elderly is on the rise, which will further increase the related medical expenditure and the burden on society and families. Therefore, in order to reduce the impact of age on posture control, it is particularly important to choose an exercise method to improve posture stability. Currently, the research on improving posture stability through exercise has received more attention. A number of studies have confirmed that yoga, physical training, water gymnastics, strength training and whole body vibration training can be used as interventions to prevent falls in the elderly. Most of the sports described above require safety monitoring, rely on special equipment, and require specific venues. In addition to these exercise choices, Tai Chi with traditional Chinese characteristics has also been proved to improve muscle strength and posture stability of the middle-aged and elderly. Tai Chi is a slow and gentle exercise mode, which has the characteristics of small requirements for the venue, high persistence, easy to carry out and low cost. It plays an important role in improving the postural stability of the elderly and reducing the incidence of falls in the elderly. At present, there are few studies on the effects of Tai Chi on the postural stability of the elderly. Therefore, this paper will summarize the published articles on the effects of Tai Chi on the postural stability of the human body, and more comprehensive understanding of the mechanism of the role of Tai Chi in improving the postural stability of the elderly, so as to provide evidence for the promotion and practice of Tai Chi. Methods: This paper mainly uses the method of literature to search PubMed, China National Knowledge Infrastructure, Baidu Scholar and Wanfang Data, collect articles on Tai Chi to prevent falls and improve posture control of the elderly, and summarize the results of the literature research. Results: This paper will analyze the mechanism of Tai Chi in improving the postural stability of the elderly from three aspects: sensory afferent, central integration and motor control. Effect of Tai Chi on sensory input 1 Proprioceptive During Tai Chi exercise, the practitioner is in a state of slow movement, and it is necessary to pay attention to the changes of limb position, movement direction and rhythm, in which motion and position sensation can be exercised. Accurate motion and position perception can provide the central nervous system with the information needed to better control standing balance. Moreover, regular exercise can reduce the stretch reflex delay and improve the sensitivity of muscle spindles, thus making proprioceptive input information more reliable. 2 Plantar Pressure Sense In the process of practicing Tai Chi, the maximum plantar peak pressure occurs in the toe area, continuous practice can improve the sensory feedback of the toe region. At the same time, the human body senses the plantar pressure distribution to help the practitioner adjust the center of gravity to maintain posture balance. Therefore, long-term practice of Tai Chi can increase the body's control over the center of gravity, so as to improve the balance ability and reduce the risk of fall. 3 Visual Vision is an important factor affecting balance ability. Tai Chi exercise pay attention to hand-eye coordination. Sometimes hand with eye movement, sometimes alternate gaze in some movements. Long-term practice can improve visual function and maintain the compensatory function of body posture stability. 4 Vestibular Sense Tai Chi exercises include many head and body rotations and gaze movements of the hands as the head and / or trunk rotates, and sometimes accompanied by changes in support and forward direction. These actions are easy to stimulate the vestibular organs, thereby slowing down the degeneration process of vestibular receptors or increase the input proportion of sensory information, which is conducive to balance control. The influence of Tai Chi on Central Integration 1Exercise and brain plasticity Tai Chi is a typical form of physical and mental exercise, including meditation, concentration, muscle stretching and diaphragmatic breathing. Sports exercise, such as Tai Chi, can change the plasticity of the central nervous system, improve the ability of synaptic signal transmission, increase the speed of information processing, and enhance the brain's sensitivity to the sensation of extremities and the ability to control movement. 2 Tai Chi and Cognition Aging will lead to different degrees of cognitive decline in the elderly. Tai Chi uses "consciousness-guided action", which requires the practitioner to be in a state of meditation during the whole process. It can increase the attention and executive ability of the elderly, thereby improving the brain's ability to allocate attention. In the face of multi-task action, the ability of posture control is not significantly reduced and falls occur. And any form of physical exercise can increase your confidence in keeping balance. The influence of Tai Chi on Motion Control 1 Tai Chi and neuromuscular reaction It is important to maintain a good neuromuscular response during aging. Long-term Tai Chi exercise can shorten the neuromuscular reaction time of rectus femoris, gastrocnemius and tibialis anterior muscle. And the rapid start of rectus femoris and tibialis anterior muscle is helpful for the elderly to adjust their ankle posture and maintain balance when disturbed. 2 Tai Chi and muscle strength Aging is accompanied by muscle atrophy and a decline in strength. Long-term Tai Chi intervention can prevent the loss of muscle strength in the elderly, and slow down the decreasing trend of muscle strength in the elderly with age. Tai Chi always maintains the position of hip flexion and knee flexion and squatting. In the case of taking its own weight as resistance, hip, knee and ankle muscles need to participate in different degrees of centripetal, eccentric and isometric contraction, as well as the coordinated contraction of active and antagonistic muscles. It could effectively enhance the muscle strength of lower limbs and the ability to control strength. 3 Tai Chi and the Control of Center of Gravity Keeping the normal range of motion of the joint (ROM) is very important for the functional ability of daily life, especially in the elderly. In the process of exercising Tai Chi, it is accompanied by the transformation of the "xu and shi" of the lower limbs, that is, the dynamic transfer and control of the body's center of gravity between the two feet, which is beneficial for the elderly to learn to control the center of gravity and adjust their posture in the process of exercise. Moreover, hip flexion and knee flexion can reduce the body's center of gravity and increase the width of the step, so as to enlarge the supporting area and increase the stability of the body. 4 Tai Chi and joint range of motion In terms of improving the range of motion of the joint, the movements such as, Snake Creeps Down, Repulse Monkey and Needle at Sea Bottom can fully flexion and extend the hip, knee and ankle joints, while the movements such as Cross Hands, Wave Hands Like Clouds and Tuck in Robes include more hip abduction and adduction movements. Practicing a complete set of Tai Chi can extend the joint capsule, ligament and other soft tissues of the lower extremities under the action of force, and improve the flexibility and range of motion of the joint. Long-term exercise is beneficial to maintain a good range of motion of the joint and increase the strength and stiffness of the ligament. 5 Tai Chi and bones The motor function of the elderly, especially the lower limb movement and balance function, will be affected by bone mass. When practicing Tai Chi, the reaction of the heel touching the ground and the pulling force of the muscles on the attached bones will have a positive impact on the bone mineral density of the lower extremities, pelvis and lumbar vertebrae. But this beneficial effect can only be observed in long-term Tai Chi exercise. In addition, Tai Chi can also improve knee osteoarthritis and its pain, fatigue and stiffness. All these will play a positive role in maintaining or improving the posture control of the elderly. And the American College of Rheumatology also recommends Tai Chi for patients with osteoarthritis in the hands, hips and knees. Conclusion: In summary, there are three main conclusions as follows: (1) Tai Chi exercise can increase the proportion of sensory input, including proprioception, plantar pressure perception, vision, vestibular sensation and so on. When disturbed by external environment, practitioners can quickly perceive the change of body space position and provide basic information for posture control. (2) Tai Chi can not only delay the decline of physical function of the elderly, but also enhance the cognitive function of the elderly; long-term exercise helps to improve the attention, information processing speed, working memory and movement control ability of the elderly. (3) long-term Tai Chi practice can improve the ability of the elderly to perform movements, including neuromuscular response, muscle strength, range of motion of joints and bone health, etc. ; at the same time, it can also relieve joint pain and stiffness, which is helpful to maintain or improve posture control of the elderly.